2021
DOI: 10.19080/ijoprs.2021.04.555648
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Paralysis with PTSD Symptoms, Pathological Worry and Perceived Stress

Abstract: In the current study, we inspected the correlation between Sleep Paralysis and anxiety symptoms among undergraduate medical students of Pakistan. It was a questionnaire based cross-sectional study. Pre-tested, pre-designed questionnaires were administered to 100 participants and any association between sleep paralysis and PTSD symptoms, Perceived Stress, or Pathological worry was found. There was a positive correlation between Experience of Sleep Paralysis and PTSD Symptoms (d=0.319 and p=0.001), Pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Bell et al also noted a positive correlation between the severity of stress and the number of episodes of SP [62]. The same relationship was observed in a group of Pakistani medical students [63]. Denis et al pointed to stress as a significant predictor of SP in the multivariate model [64].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Bell et al also noted a positive correlation between the severity of stress and the number of episodes of SP [62]. The same relationship was observed in a group of Pakistani medical students [63]. Denis et al pointed to stress as a significant predictor of SP in the multivariate model [64].…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, in a study conducted among Pakistani medical students, a positive correlation was found between the severity of PTSD symptoms and the frequency of SP episodes [63]. Another study conducted on a group of Polish students indicated a positive correlation between the number of PTSD symptoms and the severity of psychosomatic symptoms of SP [5].…”
Section: Discussionmentioning
confidence: 91%